Determinacion de factores antinutritivos termorresistentes en leguminosas. I: Alcaloides - Muzquiz, M.=700 1 Burbano, C.; Cuadrado, C.; De la Cuadra, C.
(Es, En)
ilus., 13 ref.
Keywords: LUPINUS; ALCALOIDES; ESPAÑA